(untitled) (Global Journal of Science Frontier Research, 2018)
A large amount of sewage sludge is produced through the sewerage system in Bangladesh. A laboratory scale research work was carried out to find the potential of sewage sludge as a source of renewable Bio-Energy. This paper presents the output results of the research work which was carried out to find out the appropriate technology for biogas generation from co-digestion of sewage sludge & cow dung. The study deals with usage of different proportion of sewage sludge, cow dung and domestic sewage for four trials carrying 6% total solid concentration. For all the experiments, sewage and domestic sludge were mixed in 1:1 ratio. Anaerobic digestion was performed for 60 days at room temperature 30±4 ºC. The pH of the slurry was maintained by the system itself. The inoculum was familiarized with cow dung in the same atmosphere taken for the study and sufficient active biomass was present. It was observed in the research that, when sewage sludge mixed with other co-substrate, the significant increase in gas yield was remarkable. The performances of the reactors were analyzed on the basis of gas yield and methane yield. On the basis of the analysis of the performance of the reactors, it was found that; Trial-2 reactor containing 25% cow dung and 75% municipal sewage sludge and domestic sewage, on total solid (6% TS) of slurry gives optimum result in terms of total gas yield and methane yield (72%). Standards of Trial-2 might choose as an optimum condition for gas generation from municipal sewage sludge.